Healthcare coverage and equity – Towards Universal Health Care in Uganda - Odokonyero, Tonny; Mwesigye, Francis (Economic Policy Research Centre, 2017)
Universal Health Coverage (UHC) is a popular global health policy agenda and particularly in Uganda, the health ambition is now aligned to the UHC target. This brief provides an understanding of UHC progress in Uganda, by examining healthcare coverage and equity based on reproductive, maternal, new-born, and child health (RMCH) intervention areas. Evidence shows that coverage improved marginally over the reviewed period, although the Composite Coverage Index remained low, and regional and socio-economic disparities in coverage remained. Improving healthcare coverage is important since it corresponds to better health outcomes. To scale up healthcare coverage; interventions should aim at maintaining immunization successes and addressing existing gaps in lagging intervention areas as well as addressing inequity in coverage. Accelerating UHC is feasible if the country institutes and effectively implements a coherent set of health sector policy reforms, regarding health financing, for instance, while drawing lessons from observed successful policy efforts. The brief is from the paper “Universal health coverage in Uganda: The critical health infrastructure, healthcare coverage and equity”. It demonstrates Uganda’s progress towards UHC and equity in coverage, based on healthcare intervention areas of Reproductive, Maternal, and Child (RMC) healthcare. Composite Coverage Index (CCI) and Coverage Gap Scores (CGS) were computed using the Demographic & Health Survey data, and country comparison was conducted to draw policy lessons.